Microwave promoted solvent-free one-pot synthesis of N,N `-disubstituted urea derivatives - Jadhav, Vinod H.; Deshpande, S. S.; Borate, Hanumant B.; Wakharkar, R. D. (Journal of Chemical Research-S, 2005)
An efficient one-pot synthesis of N,N -disubstituted urea derivatives from substituted anilines, ethyl chloroformate and methyl anthranilate or methyl 3-amino-2-butenoate under microwave irradiation is reported.
Keywords: Anilines; methyl 3-amino-2-butenoate; methyl anthranilate; Microwave; urea derivatives

CNS Depressant activity of ethanol extract of sterculia guttata seeds in mice - Katade, S. R.; Misar, Ashwini V.; Mujumdar, Arvind M.; Phalgune, U. D.; Wakharkar, R. D.; Deshpande, N. R. (Indian Journal of Pharmaceutical Sciences, 2009)
Shade dried, powdered seeds of Sterculia guttata were extracted using a Soxhlet extractor with ethanol. Ethanol was removed under reduced pressure and dried to obtained crude extract. This extract was evaluated for its effect on behavioral changes, exploratory activity and barbiturate-sleeping time, using appropriate standard methods in mice. The extract exhibited dose-dependent CNS depressant activity.
Keywords: Barbitone sodium; CNS depressant activity; pentobarbitone sodium; Sterculia guttata Roxb.; Swiss albino mice

One-pot three-component kabachnik-fields synthesis of alpha-aminophosphonates using H-beta zeolite catalyst - Tillu, V. H.; Dumbre, Deepa K.; Wakharkar, R. D.; Choudhary, Vasant R. (Tetrahedron Letters, 2011)
One-pot three-component Kabachnik-Fields synthesis of alpha-aminophosphonates with high yields from the reaction between carbonyl compound, primary amine, and substituted phosphite can be carried out in a short period, using H-beta zeolite as a reusable catalyst. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Carbonyl compound; H-beta zeolite; Primary amine; Substituted phosphite

Solvent-free one-pot synthesis of sulfonephthaleins from saccharin and phenols - Tillu, V. H.; Dumbre, Deepa K.; Borate, Hanumant B.; Wakharkar, R. D.; Choudhary, Vasant R. (Synthetic Communications, 2012)
Sulfonephthaleins can be synthesized in a single pot from saccharin and phenol via the in situ formation of 2-sulfobenzoic anhydride, followed by its reaction with phenol using H2SO4 as the condensing agent, in the absence of any solvent. This solvent-free synthesis is more economical and environmentally benign.
Keywords: H2SO4; Phenols; saccharin; sulfonephthalein